Сополимеризация жидких продуктов пиролиза и акриловых мономеров; Ползуновский вестник; № 3 - Бондалетов О. В. Олег Владимирович; Бондалетова Л. И. Людмила Ивановна; Тюменцева И. В.; Бондалетов В. Г. Владимир Григорьевич; Сутягин В. М. Владимир Михайлович (2009, 2009)
Заглавие с экрана